2020
DOI: 10.3390/nu12092543
|View full text |Cite
|
Sign up to set email alerts
|

Priority Actions to Advance Population Sodium Reduction

Abstract: High sodium intake is estimated to cause approximately 3 million deaths per year worldwide. The estimated average sodium intake of 3.95 g/day far exceeds the recommended intake. Population sodium reduction should be a global priority, while simultaneously ensuring universal salt iodization. This article identifies high priority strategies that address major sources of sodium: added to packaged food, added to food consumed outside the home, and added in the home. To be included, strategies needed to be scalable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 90 publications
(102 reference statements)
0
54
0
Order By: Relevance
“…The approach of integrating low-sodium salts as a public health intervention can potentially reduce dietary sodium intake at the population level through reformulating manufactured foods with low-sodium salts, replacing cooking salt used at home or in restaurants with low-sodium salts, or a combination thereof. Thus, population uptake of low-sodium salts has been recommended as one of seven priority strategies to reduce population sodium consumption [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The approach of integrating low-sodium salts as a public health intervention can potentially reduce dietary sodium intake at the population level through reformulating manufactured foods with low-sodium salts, replacing cooking salt used at home or in restaurants with low-sodium salts, or a combination thereof. Thus, population uptake of low-sodium salts has been recommended as one of seven priority strategies to reduce population sodium consumption [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing actual Na intake may be difficult for even highly motivated consumers to achieve, given the ubiquity of added Na in the US food supply (16) . For this reason, reducing Na added to the food supply and expanding access to lower-Na food options are needed to assist consumers in lowering their Na intake (4,17) . Public health professionals and food industry partners can use data from the BRFSS optional Na module to demonstrate that the majority of adults report taking action to reduce Na intake, demonstrating potential demand for policies, interventions and products that facilitate Na reduction efforts.…”
Section: Discussionmentioning
confidence: 99%
“…reformulation of industrially produced foods, 2) consumer awareness and education, and 3) national policies that target standards for food manufacturers and providers (3,4,13). The product reformulation strategy supports sodium intake reduction through collaboration with food producers and distributors to control sodium content of packaged foods and out-of-home or restaurant foods.…”
Section: Strategies For Reducing Dietary Sodium Intakementioning
confidence: 99%
“…The Global Burden of Disease study of 2017 showed that the leading contributors to NCD-related morbidity and mortality were cardiovascular diseases such as high blood pressure, stroke, coronary heart disease, and heart failure (2). Of these, high blood pressure is one of the most significant (3). High blood pressure develops from complex and interrelated factors, including those related to modifiable behavior and lifestyle (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation